GAMBARAN POLA MAKAN DAN STATUS GIZI ANAK BALITA BERDASARKAN KARAKTERISTIK KELUARGA DI KELURAHAN SONDI RAYA KECAMATAN RAYA KABUPATEN SIMALUNGUN TAHUAN 2016 - Quin Dwi Jayanti Purba; Etti Sudaryati; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
One of family’s characteristic is the mother's job. Working mothers can lead to a decrease in nutrition.  Mainly to toddler. This is due to the time spent  for the toddler is lessen. The purpose of this research is to understand the diet pattern and nutrition status of the toddler based on the characteristics in Kelurahan Sondi Raya Kecamatan Raya Kabupaten Simalungun  in 2016.  This research was descriptive study. Population total are 303 toddlers, and  sample are 75 toddlers. Sampling techniques is proportional random sampling technique. Data which taken from the research are toddler’s characteristics, family’s characteristics ( mother’s age, mother’s education, total of family members, family gross income, and mother’s knowledge about nutrition), diet pattern, toddlers nutrition status. The collected data was analyzed descriptively. The result of the research showed that a good diet patterns for toddlers based by level energy consumption there was a tendency  found by small family members (≤4 people), high family income , working mother, high education of  mother  and mother’s knowledge of good nutrition compare by big family ( ≥ 7 persons) , mother have a job, low education of mother, low family income,  the lack of maternal nutrition knowledge. As same as toddler , which lack of nutrition, stunting, and skinny there was tendency found in big family( ≥ 7 persons), working mother, low gross family’s income, low mother’s education, and the lack of maternal nutrition knowledge compare to small family members (≤4 people), high family income , working mother, high education of  mother  and mother’s knowledge of good nutrition. Toddler who have normal nutritional status was found in families which consume good energy and protein compare to toddler who consume low energy. Health officer are expected to more focus in socialization particularly mother who has toddler in effort to increase the awareness of mother about provide food because this is to important to support toddler in increase of nutrition. Keywords:       toddler, diet patterns, nutritional status, family characteristics.